Management of restrictive and obstructive lung disease in intensive care unit: a review - Listiarini, Dian Ayu; Jufan, Akhmad Yun; Wisudarti, Calcarina Fitriani Retno (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Lung disease is broadly divided into obstructive lung disease (OLD) and restrictive lung disease (RLD). The latter is a disorder of the parenchyma, pleura, thorax, or neuromuscular walls of the lungs, characterized by decreased total lung capacity due to reduced lung distensibility. Meanwhile, OLD causes increased resistance to flow due to the blockage of part or all of the respiratory tract from the trachea to the terminal bronchioles. These two diseases' initial symptoms and signs are common, such as shortness of breath, coughing, cyanosis, respiratory muscle retractions, snoring, and fever. Early detection is needed to recognize differences in symptoms and signs, establish a diagnosis, and carry out appropriate treatment. It is essential to differentiate between RLD and OLD because they have different therapeutic management. This review aims to discuss the management of restrictive and obstructive lung disease in intensive care unit It is drawn upon various sources, including case reports, literature reviews, systematic reviews, and meta-analyses, to provide an overview of the difference between RLD and OLD to help clinicians differentiate between RLD and OLD and provide appropriate therapeutic management. Although RLD and OLD have similar signs and symptoms, they have different pathologic processes. The leading cause of RLD is a pathological condition that causes a decrease in lung compliance. Meanwhile, the primary pathological process of OLD is an increase in airway resistance, which causes typical obstructive symptoms. Addressing this area of interest can help clinicians to provide appropriate management of both pharmacotherapy and mechanical ventilation and monitoring of respiratory mechanisms